A Variant Course of Lateral Root of Median Nerve: Embryological Basis - Nagwani, Mumal; Rani, Archana; Rani, Anita; Chopra, Jyoti; Srivastava, Ajai Kumar; Sharma, Pradeep Kumar (Asian Journal of Medical Sciences, 2013)
During routine dissection of the right arm of 50 year old male cadaver, we observed that the lateral root of median nerve was piercing the coracobrachialis muscle before joining the medial root of median to form the median nerve. The lateral root of median nerve did not give any branch within the muscle and no communication was observed between musculocutaneous nerve and lateral root of median nerve within the coracobrachialis muscle or in the later course of these two nerves. The same muscle was being pierced by musculocutaneous nerve which was giving branches to the muscle. These variations are important for the anesthetists, surgeons, neurologists during surgery and anatomists during dissection in the region of axilla. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8195 Asian Journal of Medical Science, Volume-5(2) 2014: 146-150